The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/cjp2.325
|View full text |Cite
|
Sign up to set email alerts
|

KLF2 inhibits colorectal cancer progression and metastasis by inducing ferroptosis via the PI3K/AKT signaling pathway

Abstract: Krüppel‐like factor 2 (KLF2) belongs to the zinc finger family and is thought to be a tumor suppressor gene due to its low expression in various cancer types. However, its functional role and molecular pathway involvement in colorectal cancer (CRC) are not well defined. Herein, we investigated the potential mechanism of KLF2 in CRC cell invasion, migration, and epithelial–mesenchymal transition (EMT). We utilized the TCGA and GEPIA databases to analyze the expression of KLF2 in CRC patients and its correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that the PI3K/Akt signaling pathway is commonly aberrantly activated in various tumors, such as hepatocellular carcinoma 21 and colorectal cancer. 22 Evidence indicated that inhibiting the PI3K/Akt pathway may sensitize cancer cells to ferroptosis induction, offering a promising strategy to prevent carcinogenic progression. 23 Therefore, for further exploration of the underlying signaling pathway, we investigated the effects of METTL14 and FTH1 on the PI3K/Akt pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the PI3K/Akt signaling pathway is commonly aberrantly activated in various tumors, such as hepatocellular carcinoma 21 and colorectal cancer. 22 Evidence indicated that inhibiting the PI3K/Akt pathway may sensitize cancer cells to ferroptosis induction, offering a promising strategy to prevent carcinogenic progression. 23 Therefore, for further exploration of the underlying signaling pathway, we investigated the effects of METTL14 and FTH1 on the PI3K/Akt pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, KLF2 has a suppressive function in many cancers, including PCa, implying that miR-15b-3p promotes PCa progression by inhibiting KLF2. We hypothesized that KLF2 must facilitate ferroptosis because recent studies on clear cell renal cell carcinoma and colorectal cancer have reported that KLF2 induces this form of cell death via the GPX4 and PI3K/AKT pathways 29 , 39 . Our findings strongly support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…KLF2 belongs to the zinc finger family and low expression in CRC patient tissues and cell lines is associated with poor prognosis in CRC. Overexpression of KLF2 reduces GSH peroxidase 4 expression to induce ferroptosis and inhibits PI3K/AKT signaling pathway to suppress CRC cell invasion, migration and EMT [ 126 ]. Cytochrome P450 1B1 (CYP1B1), a heme sulfate monooxygenase, that is highly expressed in CRC tumor tissue.…”
Section: Ferroptosis and Crcmentioning
confidence: 99%